Regulasi Emosi Guru dan Pengelolaan Kelas di SMP Negeri 1 P.Batu - Siahaan, Amirudin; Akmalia, Rizki; Nurjannah, Dawi; Marpaung, Jelita Ramadhani; Hasibuan, Razak Hadinata; Lubis, Arif Abdul Gani (Lembaga Yasin AlSys, 2023)
Coping with emotions can be done with cognitive therapy and attitude. The cognitive approach states that the emotions that individuals feel mean what will happen from the judgment of the situation they face. The aim of the research is to provide guidelines for cognitive emotional regulation of teachers in dealing with anti-social child behavior. This research method means literature study with a qualitative approach. Basically, related literature reviews use theoretical studies and other related references using values, culture, and cultures that develop in the situations studied. Approaches to cognitive regulation of emotions that can be carried out by teachers include: (1) teachers can prohibit the regulation of children's emotions using the method of captivating emotions and prohibiting emotions; (2) teachers can provide guidance on emotional competence using a camera to convey positive and negative emotional models, how to handle children's emotions, and manifest emotions; (3) teachers can interact with children, while identifying emotions that are not sporadic in children.